Sustainable silvopastoral restoration to promote ecosystem services in Tunisia - Louhaichi, Mounir; Jamel, Kailene; Slim, Slim; Tarchi, Med Bechir; Gamoun, Mouldi; Hassan, Sawsan; Rischkowsky, Barbara (Food and Agriculture Organization of the United Nations, 2022)
this chapter is describing the The silvopastoral improvement accomplished in the region of Sbaihia, Tunisia thet relies on a sound participatory approach with full cooperation from the local population who contributed to the main decisions implemented onsite.